More than a cool illusion? Functional significance of self-motion illusion (circular vection) for perspective switches - Riecke, Bernhard E.; Feuereissen, Daniel; Rieser, John J.; McNamara, Timothy P. (Frontiers in Psychology, 2015)
Self-motion can facilitate perspective switches and “automatic spatial updating” and help reduce disorientation in applications like Virtual Reality. However, providing physical motion through moving-base motion simulators or free-space walking areas comes with high cost and technical complexity. This study provides first evidence that merely experiencing an embodied illusion of self-motion (“circular vection”) can provide similar behavioral benefits as actual self-motion: Blindfolded participants were asked to imagine facing new perspectives in a well-learned room, and point to previously-learned objects. Merely imagining perspective switches while stationary yielded worst performance. When perceiving illusory self-rotation to the novel perspective, however, performance improved significantly and yielded performance similar to actual rotation. Circular vection was induced by combining rotating sound fields (“auditory vection”) and biomechanical vection from stepping along a carrousel-like rotating floor platter. In sum, illusory self-motion indeed facilitated perspective switches and thus spatial orientation, similar to actual self-motion, thus providing first compelling evidence of the functional significance and behavioral relevance of vection. This could ultimately enable us to complement the prevailing introspective vection measures with behavioral indicators, and guide the design for more affordable yet effective Virtual Reality simulators that intelligently employ multi-modal self-motion illusions to reduce the need for costly physical observer motion.